Breaking Out of a Niche: Lessons for SMRs from Sustainability Transitions Studies. (2nd September 2021) - Iakovleva, Mariia; Rayner, Jeremy; Coates, Ken
Abstract: Small modular reactors (SMRs) are currently framed as a clean energy innovation with a vital role to play in decarbonizing power production. We review two popular sustainability transitions frameworks—strategic niche management and technological innovation systems— for case studies of analogous clean technology innovations. We focus on those that include policy-relevant recommendations that could be applied to the challenges posed by successfully scaling up SMRs from prototypes to commercial production. Particular attention is paid to how each approach understands the linkages between technology and the broader social and economic context. Innovative features of this paper include a systematic review of the lessons from renewable energy case studies for engagement with policy practitioners; reflections on the challenges of applying Euro-centric approaches in the sustainability transitions literature to non-European environments, including remote, northern, and indigenous communities; and some preliminary lessons for policy development that reflect the current situation with SMRs and support evidence-informed decision making in communities currently considering SMRs as part of a future clean energy mix.